NOVELTY ARCHITECTURE AND MATHEMATICS IN AN IRANIAN MOSQUE - Behnamian, Sara; Behnamian, Saman; Fogh, Fatemeh; Pashaei, Firooz; Saran, Malihe Mahin (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2020)
Islamic architecture, particularly mosques architecture, has mainly been the focus of many architectural exhibitions in Muslim-majority countries. Recently, it has been influenced by novelty architecture and has been evolvedÂ into elaborate structures. Quds mosque in Tehran, Iran, is a picturesque architecture feat of a modern outlook that came under a lot of criticism for abandoning the traditional symbols of Islamic architecture. This study observes the Quds mosque from a mathematical standpoint using fractals as the method. Fractals are geometric constructions that exhibit similar or identical characteristics by order of magnitude. Rescaling a prominent architectural pattern is also a noticeable subject that considers Quds mosque from this point of view. This study shows that the Quds mosque used fractal principles; self-similarity and congruency. Those are applied in the roof form by using a triangle form on each side.